PERANCANGAN ILUSTRASI STIKER DAN LAYOUT BUKU AKTIVITAS PENDERITA DEPRESI MAYOR - FITRIA WULANDA, Dr. Budiwirman, M.Pd., Hendra Afriwan, S.Sn. M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The book as the main object will convey the message of patients with major depressive disorders with sticker illustrations, then cause-effect and the initial solution to the problems faced by sufferers of major depressive disorders. Things that cannot be handled orally, can be changed in writing in which there is a form of activity. Thus conveying messages and lessons through media activity books will greatly help the patient's family and the patient themselves in dealing with major depressive disorders.In designing a book for major depression sufferers, the authors collected data through the method of observation and literature study and some empirical experiences that the author had experienced. The author processes the data using the 5W1H method. The results of the analysis are used as benchmarks in determining the layout. This book is done digitally using the Comic Intuos Pen Tablet type Comic and Adobe Photoshop CC 2018 software and Adobe Indesign CC 2018. The book will be in the form of stickers that are the lifeblood of the contents of the book. The style of illustration used on the stickers is manga, which is the style of chibi and emoji.Activity Books for Major Depression Sufferers are printed in the form of colored books with a total of 100 pages in A5 size with 100gsm HVS paper. This design is also supported by supporting media in the form of x-banners, posters, stickers, T-shirts, totebags, pins and acrylic key chains.Keywords: Books, Activity Books, Depression, Medical